The effect of the problem-oriented project-based learning (POPBL) model on high school students' collaboration skills on metabolic and cell division materials - Riza Farahdika Filmi; Ibrohim Ibrohim; Sitoresmi Prabaningtyas (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2024)
The Problem-Oriented Project-Based Learning (POPBL) model is believed to be a learning approach that can effectively facilitate students in developing 21st-century skills. Adopting a student-centered approach is essential to engage students actively in learning activities. This study investigates the impact of the POPBL model on collaboration skills related to metabolic material and cell division. The research employs a quasi-experiment design, and the instrument used for data collection is a collaborative questionnaire that includes peer assessment and self-assessment. Analysis of students' collaboration skills, based on the average collaboration skills calculation, indicates that the experimental class using the POPBL learning model outperformed the control class. Prerequisite tests confirmed that the data are normally distributed and homogeneous. The ANCOVA data analysis results show a significant impact of the learning model treatment, with a significance value of p = 0.000<α = 0.05. This indicates that the hypothesis is accepted, and H0 is rejected. Consequently, there are significant differences in collaboration skills between the experimental class (XII MIPA 3) and the control class (XII MIPA 2). These research findings are expected to serve as a valuable reference for educators seeking effective learning models to enhance the quality of biology education, particularly in improving students' collaboration skills.Abstrak. Model pembelajaran Problem Oriented Project Based Learning (POPBL) diyakini dapat pembelajaran yang dapat memfasilitasi siswa agar dapat memberdayakan keterampilan abad-21. Pembelajaran dengan student center perlu dilakukan agar siswa terlibat aktif dalam kegiatan pembelajaran. Penelitian ini bertujuan untuk mengetahui pengaruh antara model POPBL terhadap keterampilan kolaborasi pada materi metabolisme dan pembelahan sel. Metode penelitian yang digunakan dalam penelitian ini adalah quasy experiment, dan instrument yang digunakan dalam penelitian ini adalah angket kolaborasi (Peer assessment dan self assessment). Analisis data keterampilan kolaborasi siswa dengan dengan hasil perhitungan rerata keterampilan kolaborasi menunjukkan kelas eksperimen yang menggunakan model pembelajaran Problem Oriented Project Based Learning (POPBL) lebih tinggi daripada kelas kontrol. Uji prasyarat terbukti data berdistribusi normal dan homogen. Hasil nilai analisis data ANCOVA memiliki nilai signifikansi perlakuan model pembelajaran yaitu p =0,000<α =0,05 artinya hipotesis diterima dan H0 ditolak. Ini menunjukkan bahwa terdapat perbedaan yang signifikan keterampilan kolaborasi anatara kelas eksperimen (XII MIPA 3) dan kelas kontrol (XII MIPA 2). Hasil penelitian ini diharapkan dapat dijadikan sebagai rujukan model pembelajaran yang memberikan solusi dalam upaya meningkatkan kualitas pembelajaran biologi khususnya untuk meningkatkan keterampilan kolaborasi pada siswa.